2010
DOI: 10.1186/1756-9966-29-110
|View full text |Cite
|
Sign up to set email alerts
|

Cellular apoptosis susceptibility (CSE1L/CAS) protein in cancer metastasis and chemotherapeutic drug-induced apoptosis

Abstract: The cellular apoptosis susceptibility (CSE1L/CAS) protein is highly expressed in cancer, and its expression is positively correlated with high cancer stage, high cancer grade, and worse outcomes of patients. CSE1L (or CAS) regulates chemotherapeutic drug-induced cancer cell apoptosis and may play important roles in mediating the cytotoxicities of chemotherapeutic drugs against cancer cells in cancer chemotherapy. CSE1L was originally regarded as a proliferation-associated protein and was thought to regulate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 75 publications
3
34
0
Order By: Relevance
“…Scale bar 50 lm high cancer stage, and worse patient outcomes (Behrens et al 2001(Behrens et al , 2003Tai et al 2010b). The results of recent studies have shown that CSE1L can mediate the secretion and metastasis of cancer cells (Liao et al 2008a;Tsao et al 2009;Tung et al 2009;Stella Tsai et al 2010;Tung et al 2010;Tai et al 2010a). Therefore, the distribution of CSE1L in cell-cell junctions between epithelial cells in colorectal glands may assist with E-cadherin-mediated epithelial cell polarity formation and maintenance in the glands, aiding gland architectural organization and the proper physiological functioning of the glands.…”
Section: Discussionmentioning
confidence: 90%
“…Scale bar 50 lm high cancer stage, and worse patient outcomes (Behrens et al 2001(Behrens et al , 2003Tai et al 2010b). The results of recent studies have shown that CSE1L can mediate the secretion and metastasis of cancer cells (Liao et al 2008a;Tsao et al 2009;Tung et al 2009;Stella Tsai et al 2010;Tung et al 2010;Tai et al 2010a). Therefore, the distribution of CSE1L in cell-cell junctions between epithelial cells in colorectal glands may assist with E-cadherin-mediated epithelial cell polarity formation and maintenance in the glands, aiding gland architectural organization and the proper physiological functioning of the glands.…”
Section: Discussionmentioning
confidence: 90%
“…Plays an important role in regulating cancer cell proliferation and apoptosis, where up regulation is correlated with a worsened patient outcome (66).…”
Section: Preparation Of Dotap-modified Plga Nanoparticlesmentioning
confidence: 99%
“…CSE1L is expressed in various tissues, and particularly it is highly expressed in most cancer (Tai et al, 2010a;Brinkmann et al, 1995). The expression level CSE1L is positively correlated with high tumor stage, high tumor grade, and worse outcomes of cancer patients (Tai et al, 2010a).…”
Section: Expressionmentioning
confidence: 99%
“…The expression level CSE1L is positively correlated with high tumor stage, high tumor grade, and worse outcomes of cancer patients (Tai et al, 2010a). The increased expression of CSE1L in cancer is mainly due to the amplification of the copy number of the CSE1L gene in cancer tissue (Tai et al, 2010a).…”
Section: Expressionmentioning
confidence: 99%